Model identification methodology for fluid-based inerters. (June 2018) - Liu, Xiaofu; Jiang, Jason Zheng; Titurus, Branislav; Harrison, Andrew
Highlights: A modelling procedure of the fluid-based inerter is established. An experimental sequence is presented for more accurate modelling. An experimental set-up is introduced to accurately measure the pressure drop. A dynamic model is obtained for a helical-tube fluid inerter prototype. Abstract: Inerter is the mechanical dual of the capacitor via the force-current analogy. It has the property that the force across the terminals is proportional to their relative acceleration. Compared with flywheel-based inerters, fluid-based forms have advantages of improved durability, inherent damping and simplicity of design. In order to improve the understanding of the physical behaviour of this fluid-based device, especially caused by the hydraulic resistance and inertial effects in the external tube, this work proposes a comprehensive model identification methodology. Firstly, a modelling procedure is established, which allows the topological arrangement of the mechanical networks to be obtained by mapping the damping, inertance and stiffness effects directly to their respective hydraulic counterparts. Secondly, an experimental sequence is followed, which separates the identification of friction, stiffness and various damping effects. Furthermore, an experimental set-up is introduced, where two pressure gauges are used to accurately measure the pressure drop across the external tube. The theoretical models with improved confidence are obtained using the proposed methodology for a helical-tube fluid inerter prototype. The sources of remaining discrepancies are further analysed.